Trivialization and Public Opinion Slogans, Substance, and Styles of Thought in the Age of Complexity - Bubak, Oldrich; Jacek, Henry; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
"Taking a transdisciplinary view, this innovative title serves both as an important addition and a challenge to the existing research in communications and in social sciences more generally...I highly recommend this book to all readers seeking a more complete picture of change, so needed in our increasingly complex society." -D. R. F. Taylor, Distinguished Research Professor, Carleton University, Canada "This is an important book that should be read by anyone concerned about the current state of political discourse in the industrialized democracies...We should all learn to listen and to ask: 'how do you know?'" -Fred Fletcher, Professor Emeritus of Communication Studies and Political Science, York University, Canada Centering on public discourse and its fundamental lapses, this book takes a unique look at key barriers to social and political advancement in the information age. Public discourse is replete with confident, easy to manage claims, intuitions, and other shortcuts; outstanding of these is trivialization, the trend to distill multifaceted dilemmas to binary choices, neglect the big picture, gloss over alternatives, or filter reality through a lens of convenience-leaving little room for nuance and hence debate. Far from superficial, such lapses are symptoms of deeper, intrinsically connected shortcomings inviting further attention. Focusing primarily on industrialized democracies, the authors take their readers on a transdisciplinary journey into the world of trivialization, engaging as they do so the intricate issues borne of a modern environment both enabled and constrained by technology. Ultimately, the authors elaborate upon the emerging counterweights to conventional worldviews and the paradigmatic alternatives that promise to help open new avenues for progress.
Part I: On Trivialization -- Chapter 1: Introduction -- Chapter 2: Trivialization -- Chapter 3: The Uneasy World of "isms" -- Part II: Opinions and Their Public -- Chapter 4: Democracy (Re)imagined -- Chapter 5: Bringing in the Public.-Chapter 6: What We Can Learn -- Part III: Approaching Complexity -- Chapter 7: Assumptions and Precautions.-Chapter 8: Into a New Paradigm -- Chapter 9: Transformations -- Part IV: Shifting Cultures -- Chapter 10: Beyond Folklore -- Chapter 11: Thinking Change. .
Keywords: Knowledge, Sociology of; Culture; Mass media; Political science; Political planning; Sociology of Knowledge and Discourse; Sociology of Culture; Media Sociology; Governance and Government; Public Policy